2013
DOI: 10.1155/2013/535742
|View full text |Cite
|
Sign up to set email alerts
|

“Intensity-Response” Effects of Electroacupuncture on Gastric Motility and Its Underlying Peripheral Neural Mechanism

Abstract: The aim of this study was to explore the “intensity-response” relationship between EAS and the effect of gastric motility of rats and its underlying peripheral neural mechanism by employing ASIC3 knockout (ASIC3−/−), TRPV1 knockout (TRPV1−/−), and C57BL/6 mice. For adult male Sprague-Dawley (n = 18) rats, the intensities of EAS were 0.5, 1, 3, 5, 7, and 9 mA, respectively. For mice (n = 8 in each group), only 1 mA was used, by which C fiber of the mice can be activated. Gastric antrum motility was measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 24 publications
0
21
0
1
Order By: Relevance
“…Similar findings have been reported in previous studies. [5][6][7][8][9][10] Unlike in the small intestine, the IM -induced delay in gastric emptying was unrelated to the gastric slow wave. This was because IM did not alter gastric DF, DP, or rhythmicity in comparison with the control rats (same abdominal surgery without IM).…”
Section: Discussionmentioning
confidence: 95%
“…Similar findings have been reported in previous studies. [5][6][7][8][9][10] Unlike in the small intestine, the IM -induced delay in gastric emptying was unrelated to the gastric slow wave. This was because IM did not alter gastric DF, DP, or rhythmicity in comparison with the control rats (same abdominal surgery without IM).…”
Section: Discussionmentioning
confidence: 95%
“…TRPV1 receptor was involved in the regulation process of EAS [5]. Previous studies also suggested that acupuncture at the lower limbs stimulated gastric motility via vagal cholinergic pathways, while acupuncture at the abdomen inhibited gastric motility via sympathetic pathways in rats [9].…”
Section: Discussionmentioning
confidence: 99%
“…After an overnight fast, the animals were anesthetized with 10% urethane (1.0–1.2 g/kg, via intraperitoneal route). Surgical procedures were carried out as described previously [ 5 ]. Briefly, a tracheotomy was performed to maintain an open, low resistance airway.…”
Section: Methodsmentioning
confidence: 99%
“…The activation of different afferent fibers could produce distinct effects on certain conditions [ 2 4 ]. Our previous work showed that modulatory effects of electroacupuncture on gastric motility were closely related to the stimulating intensity, which the A δ fiber and TRPV1 receptor were involved in [ 5 ].…”
Section: Introductionmentioning
confidence: 99%